TRADISI DANDANGAN SEBAGAI KAJIAN PEMBELAJARAN DALAM MENDUKUNG PENCAPAIAN VISI UNIVERSITAS KEBUDAYAAN (Studi pada Mata Kuliah Konsep Ilmu Pengetahuan Sosial) - Erik Aditia Ismaya; Santoso Santoso (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2019)
The purpose of this study is to analyze the Dandangan Tradition while simultaneously analyzing the meaning and value of the Dandangan Tradition as a study of learning in supporting the achievement of the vision of the University of Culture. This study uses qualitative descriptive research and field studies. The main data obtained directly through interviews with informants. observation, literature study and documentation.. The validity of the source triangulation technique is used. Data analysis was performed through inductive-descriptive-verivative analysis. The results of the study showed the Dalih Tradition from the sound of drum beating. The sound of the drum that reads "dang dang dang" compilation is hit in the middle and the sound "dug dug dug" compilation is hit on the edge of the drum then turns into the start of the month of Ramadan castle and is also known as Dandangan. Other opinions mention that Dandangan is taken from the word Ndang, which is obtained from the sound / sound of Bedhug beating, so that the sound of Ndang-Ndang (come on) which is heard by all the people of Kudus and also for Kudus to come and flock to be visited at Menara Mosque can be read from Sunan. Kudus came in order to welcome the Holy Month of Ramadan. The Meanings and Values of the Dandangan Tradition include 1) the early momentum of the holy month of Ramadan, 2) enthusiasm and joy, 3) regular and continuous patterns, 4) harmony, mutual support and the spirit of togetherness, 5) the momentum of the immediate rise, 6) the relationship between worldly life and the afterlife, 7) The inner atmosphere of the Holy community which is full of joy and joy to welcome the coming of Ramadan.